Assessing genetic counselors' graduate school education and training in congenital heart defects. Issue 3 (7th December 2021) - Ahmad, Aaliya; Fitzgerald‐Butt, Sara M.; Ware, Stephanie M.; Ison, Hannah E.; Elmore, Lindsey R.; Helm, Benjamin M.
Abstract: Genetic counselors are one of the many providers involved in caring for patients with congenital heart defects (CHDs); however, little is known about the cardiovascular genetics training they receive by their graduate programs. To explore the recalled education experiences regarding CHDs by practicing genetic counselors, we surveyed graduates of programs primarily accredited by the American Council on Genetic Counseling (ACGC) about their graduate training in this area, the depth of CHD‐specific education they received, and whether CHDs are a substantial referral indication in their current practice. Genetic counselors were recruited from the National Society of Genetic Counselors and Twitter ( n  = 112), and participants reflecting multiple specialties and 35 graduate programs completed an online survey which included questions about fieldwork placements and lectures in cardiovascular genetics, exposure to classification schemes regarding cardiac embryology, and education in counseling strategies for CHDs and CHD‐related topics during their graduate training. When asked whether CHDs are a substantial referral indication seen in their current practice, 55% (62/112) responded yes. Most participants (79%, 88/112) recalled receiving some education about CHDs, but 91% (80/88) reported receiving little to no education regarding embryologic classification of CHDs and how to apply classification schemes to their counseling. Both participating prenatal and pediatric GCs reported that CHDs can be a common referral indication, yet they reported receiving limited education on teratogens associated with CHDs, family screening recommendations, and recurrence risk counseling for CHDs. Based on participant responses, the majority of respondents reported receiving sufficient education on syndromes with CHDs which can be beneficial in specialties such as pediatrics. This exploratory study provides insight into opportunities to further support genetic counseling educational opportunities for CHDs. These findings suggest genetic counseling graduate programs could consider implementing education on CHD counseling strategies as a standardized component of the curriculum and that practicing genetic counselors could benefit from educational opportunities and resources with updated information on this topic.